2006
DOI: 10.1021/jo061328z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polymer-Bound 4-Acetoxy-3-phenylbenzaldehyde Derivatives:  Applications in Solid-Phase Organic Synthesis

Abstract: Aminomethyl polystyrene resin was reacted with 4-(5′-formyl-2′-hydroxyphenyl)benzoic acid and 4-(5′-formyl-2′-hydroxyphenyl)phenyl propionic acid, respectively, in the presence of 1-hydroxybenzotriazole and 1,3-diisopropylcarbodiimide to yield polymer-bound benzaldehydes. The phenolic group in resins was acetylated with acetic anhydride to afford two polymer-bound 4-acetoxybenzaldehydes. The reductive amination of polymer-bound linkers by amines and sodium triacetoxyborohydride, followed by sulfonylation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…It should be noted that the gel–sol transition is reversible. Through increasing the HCl concentration of the solution to 6 M , hydrogels could be re‐formed ( Figure ) since the boronate esters have been demonstrated to hydrolyze under these conditions 41, 42…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the gel–sol transition is reversible. Through increasing the HCl concentration of the solution to 6 M , hydrogels could be re‐formed ( Figure ) since the boronate esters have been demonstrated to hydrolyze under these conditions 41, 42…”
Section: Resultsmentioning
confidence: 99%
“…28 Our research on the solid-phase synthesis of organophosphorus and organosulfur compounds revealed that the polymer-bound p -acetoxybenzyl alcohol containing amide linker ( 5 ) was more stable than polymer-bound N -Boc p -acetoxybenzyl alcohol even in basic conditions and was used to generate sulfonamides and other organophosphorus compounds in high yields and without the need for extensive purifications of final products. 29,30 Thus, polymer-bound linker 5 instead of polymer-bound N -Boc p -acetoxybenzyl alcohol was selected for the reaction with β-triphosphitylating reagent 6 to generate a new polymer-bound β-triphosphitylating reagent 7 that was used for preparation of nucleoside β-triphosphates including two novel compounds 3 and 4 (Scheme 1). …”
mentioning
confidence: 99%
“…24 Our earlier studies revealed the application of polymer-bound p -acetoxybenzyl alcohol linkers in the synthesis of a diverse number of compounds 25. Polymer-bound linker 7 was selected for immobilization of reagent 6 .…”
mentioning
confidence: 99%